Genetic analysis of atherosclerosis identifies a major susceptibility locus in the major histocompatibility complex of mice. (November 2016) - Grainger, Andrew T.; Jones, Michael B.; Li, Jing; Chen, Mei-Hua; Manichaikul, Ani; Shi, Weibin
Abstract: Background and aims: Recent genome-wide association studies (GWAS) have identified over 50 significant loci containing common variants associated with coronary artery disease. However, these variants explain only 26% of the genetic heritability of the disease, suggesting that many more variants remain to be discovered. Here, we examined the genetic basis underlying the marked difference between SM/J- Apoe −/− and BALB/cJ- Apoe −/− mice in atherosclerotic lesion formation. Methods: 206 female F2 mice generated from an intercross between the two Apoe −/- strains were fed 12 weeks of western diet. Atherosclerotic lesion sizes in the aortic root were measured and 149 genetic markers genotyped across the entire genome. Results: A significant locus, named Ath49 (LOD score: 4.18), for atherosclerosis was mapped to the H2 complex [mouse major histocompatibility complex (MHC)] on chromosome 17. Bioinformatic analysis identified 12 probable candidate genes, including Tnfrsf21, Adgrf1, Adgrf5, Mep1a, and Pla2g7 . Corresponding human genomic regions of Ath49 showed significant association with coronary heart disease. Five suggestive loci on chromosomes 1, 4, 5, and 8 for atherosclerosis were also identified. Atherosclerotic lesion sizes were significantly correlated with HDL but not with non-HDL cholesterol, triglyceride or glucose levels in the F2 cohort. Conclusions: We have identified the MHC as a major genetic determinant of atherosclerosis, highlighting the importance of inflammation in atherogenesis. Highlights: A female F2 cross was generated from SM/J and BALB/cJ Apoe−/− mice. A significant locus, named Ath49, for atherosclerosis was mapped to the H2 complex [mouse major histocompatibility complex (MHC)] on chromosome 17. Corresponding human genomic regions of Ath49 showed significant association with coronary heart disease. Five suggestive loci for atherosclerosis were also identified. The findings highlight the importance of inflammation in atherogenesis.